The Work of Professional Football - Roderick, Martin (Taylor & Francis, 2006)
A long-term study providing rare insights into the precarious career and ordinary working culture of professional footballers. Away from the celebrity-obsessed media gaze, the work of a professional footballer is rarely glamorous and for most players a career in football is insecure and short-lived. A former professional, Martin Roderick$1 (Bs familiarity with the world of football is the foundation for this privileged research into a world that is typically closed to the public gaze and ignored by media reportage and academic research which prefers to focus on a small, unrepresentative group of elite players. Key themes explored within the text include: the culture of work in professional football the changing identity, orientation and expectations of players during their careers the fragile and uncertain nature of professional sport careers the performance and dramatic aspects of a career under public scrutiny the role of relationships with managers, owners, support staff and partners players' responses to the insecurities inherent in professional football such as injury, ageing, performance and transfer. The text deals with a wide range of issues of interest to sports students and academics, particularly those with a focus on the sociology of sport but also including sport development, sport management and coaching studies. The text will also be of interest to researchers in the fields of careers, industrial relations and the sociology of work.s
English
Keywords: Sociology; Sports & outdoor recreation; American football; club; physiotherapists; doctors; labour; love; premiership; player; premier; league; parker